Improvement of green procurement performance in the global supply chain: evidence from enterprise resource planning and social network analysis - Muhammad Shabir, Shaharudin; Syafiqa, Suhaimi; Fernando, Yudi; Wan Ahmad Fauzi, Wan Husain; Suparman, . (Penerbit Universiti Malaysia Pahang, 2021)
The purpose of this paper is to present a plan on how to improve the operational efficiency of the company during the Covid-19 period. Previous research has been reviewed in order to gain further knowledge of the problem; primarily on the operational performance, as well as on the supply chain management of the company. The results have shown that, on the basis of a social network analysis, the Procurement Engineer is the most influential individual in the management of information within the organization, where the Procurement Engineer is also the employee who has a strong link with the transfer of data to top management, the Ishikawa diagram indicates that the present environment is the primary cause of the company's problems in finding products, while the Tree diagram shows the only approach to the issue of insufficient employees is by supplying training for new or existing workers or by assigning staff from another department to serve permanently in a department where there is a lack of staff. In addition, the Enterprise Resource Planning (ERP) framework will strengthen the green supply chain management of the business as it will help to reduce the loss of time waiting for or processing the company's materials, thereby reducing the cost as well. This research offers proof of the pre-Covid 19and post-Covid 19 impacts on green supply chain operational performance.